Joubert Syndrome and Related Disorders: Spectrum of Neuroimaging Findings in 75 Patients - Poretti, A.; Huisman, T.A.G.M.; Scheer, I.; Boltshauser, E. (American Journal of Neuroradiology, 2011)
SUMMARY: VH and MTS are the neuroimaging hallmarks of JSRD. We aimed to look at the full spectrum of neuroimaging findings in JSRD and reviewed the MR imaging of 75 patients with JSRD, including 13 siblings and 4 patients with OFD VI. All patients had VH and enlargement of the fourth ventricle. The degree of VH and the form of the MTS were variable. In most patients, the cerebellar hemispheres were normal and the PF was enlarged. Brain stem morphology was abnormal in 30% of the patients. Supratentorial findings included hippocampal malrotation, callosal dysgenesis, migration disorders, cephaloceles, and ventriculomegaly. All patients with OFD VI had a similar pattern, including HH in 2 patients. No neuroimaging-genotype correlation could be found. The wide neuroimaging spectrum in our patients supports the heterogeneity of JSRD. Neuroimaging differences in siblings represent intrafamilial heterogeneity. Due to the absence of a correlation with genotype, neuroimaging findings are of limited value in classifying patients with JSRD. CCcorpus callosumHHhypothalamic hamartomaIFinterpeduncular fossaJSJoubert syndromeJSRDJoubert syndrome and related disordersMTSmolar tooth signOFD VIoral-facial-digital syndrome type VIPFposterior fossaPMGpolymicrogyriaSCPsuperior cerebellar pedunclesVHvermian hypoplasia